Weiterentwicklung eines physikdidaktischen Tests zum Online-Assessment - Jordans, Melanie; Zeller, Jannis; Große-Heilmann, Rike Isabel; Riese, Josef (Unsicherheit als Element von naturwissenschaftsbezogenen Bildungsprozessen. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung virtuell 2021)

Proaktives Management von Anforderungsänderungen in der Entwicklung komplexer technischer Systeme - Oleff, Christian
Anforderungsänderungen sind ein wesentlicher Grund für Ineffizienzen und Projektfehlschläge in der Entwicklung komplexer technischer Systeme. Proaktives Management von Anforderungsänderungen hat das Potenzial, den Umgang mit Anforderungsänderungen effizienter zu gestalten. Dafür ist ein systematischer Ansatz erforderlich, der eine ganzheitliche Bewertung und Handhabung des Änderungsrisikos im industriellen Entwicklungskontext ermöglicht. Im Rahmen dieser Dissertation wird mit der ProMaRC-Methodik ein neuartiger Ansatz für das proaktive Management von Anforderungsänderungen vorgestellt. Die Methodik wurde in enger Zusammenarbeit mit Industrieanwender:innen aus der Automobilindustrie entwickelt und anhand von fünf Fallstudien validiert. Mittels automatisierter Abhängigkeitsanalyse auf Grundlage künstlicher Intelligenz wird der Anwendungsaufwand gegenüber bestehenden Ansätzen reduziert. Die teilautomatisierte Bewertung und Handhabung der Änderungswahrscheinlichkeit und -auswirkung erfolgt anhand eines modifizierten PageRank-Algorithmus und umfasst erstmalig alle für die Risikoanalyse relevanten Einflussfaktoren. Die Validierung belegt, dass durch die ProMaRC-Methodik eine überzeugende Kombination aus praxistauglichem Anwendungsaufwand und Vollständigkeit der Analyse erzielt wird. Damit erschließt diese Dissertation das bisher kaum beachtete Forschungsfeld des proaktiven Managements von Anforderungsänderungen und fördert eine effizientere Produktentwicklung.

Automatisierte dezentrale Produktionssteuerung für cyber-physische Produktionssysteme mit digitaler Repräsentation der Beschäftigten - Pöhler, Alexander
In dieser Arbeit wird die Entwicklung einer dezentralen Produktionssteuerung mit digitaler Repräsentation zur Anwendung in cyber-physischen Produktionssystemen (CPPS) beschrieben. Die dezentrale Produktionssteuerung geschieht hierbei selbstorganisiert, da sie die Einlastung und Umplanung von Aufträgen sowie die Koordination zwischen den einzelnen Produktionselementen selbstständig übernimmt. Dies erlaubt die automatisierte Steuerung von CPPS. Dabei spielen die Beschäftigten in dieser Betrachtung eine wesentliche Rolle. Ihre Bedürfnisse und Wünsche werden von dem Steuerungssystem berücksichtigt. Dafür wurde das Konzept der digitalen Repräsentation von Beschäftigten entwickelt. Diese Repräsentation erlaubt den individuellen Eingriff von Beschäftigten bei Entscheidungen von dem Steuerungssystem. Das automatisierte dezentrale Steuerungssystem wurde in einer Laborumgebung, die zu einem CPPS umgebaut wurde, implementiert. Darauf basierend wurde eine zweistufige Validierung durchgeführt. Ein Teil der Validierung findet durch eine reale Umsetzung in einem Labor statt, bei der ein Vergleich zu dem vorher im Labor eingesetzten zentralen Produktionssteuerungssystem gezogen wird. Die zweite Validierung erfolgt mit Hilfe einer Simulationsumgebung. Dabei konnte die Implementierung der Selbstorganisation und eine Steigerung der Liefertreue der dezentralen Produktionssteuerung gegenüber heutzutage üblicherweise eingesetzten Verfahren nachgewiesen werden.

Mauro Luiz Engelmann: Reading Wittgenstein’s Tractatus. Cambridge: Cambridge University Press, 2021 - Milkov, Nikolay (Nordic Wittgenstein Review)

Argumentieren im Widerstand - Markewitz, Friedrich (Sprache in Politik und Gesellschaft. Perspektiven und Zugänge)

Optimization of optical waveguide antennas for directive emission of light - Farheen, Henna; Leuteritz, Till; Linden, Stefan; Myroshnychenko, Viktor; Förstner, Jens (Journal of the Optical Society of America B)
Optical traveling wave antennas offer unique opportunities to control and selectively guide light into a specific direction, which renders them excellent candidates for optical communication and sensing. These applications require state-of-the-art engineering to reach optimized functionalities such as high directivity and radiation efficiency, low sidelobe levels, broadband and tunable capabilities, and compact design. In this work, we report on the numerical optimization of the directivity of optical traveling wave antennas made from low-loss dielectric materials using full-wave numerical simulations in conjunction with the particle swarm optimization algorithm. The antennas are composed of a reflector and a director deposited on a glass substrate, and an emitter placed in the feed gap between them serves as an internal source of excitation. In particular, we analyze antennas with rectangular- and horn-shaped directors made of either hafnium dioxide or silicon. The optimized antennas produce highly directional emissions due to the presence of two dominant guided TE modes in the director in addition to leaky modes. These guided modes dominate the far-field emission pattern and govern the direction of the main lobe emission, which predominately originates from the end facet of the director. Our work also provides a comprehensive analysis of the modes, radiation patterns, parametric influences, and bandwidths of the antennas, which highlights their robust nature.
Keywords: tet_topic_opticalantenna

Numerical analysis of the coherent mechanism producing negative polarization at backscattering from systems of absorbing particles - Alhaddad, Samer; Grynko, Yevgen; Farheen, Henna; Förstner, Jens (Optics Letters)
We study a double-scattering coherent mechanism of negative polarization (NP) near opposition that is observed for powder-like surfaces. The problem is solved numerically for absorbing structures with irregular constituents, cubes, spheres, and ellipsoids larger than the wavelength of incident light. Our simulations show that double scattering between two random irregular particles shows weak NP. Adding one more particle significantly increases the relative contribution of double scattering which enhances NP. Simulations with regular shapes and controlled geometric parameters show that the interference mechanism is sensitive to the geometry of the scattering system and can also result in no polarization or even strong enhancement of positive polarization at backscattering.
Keywords: tet_topic_scattering

Broadband optical Ta2O5 antennas for directional emission of light - Farheen, Henna; Yan, Lok-Yee; Quiring, Viktor; Eigner, Christof; Zentgraf, Thomas; Linden, Stefan; Förstner, Jens; Myroshnychenko, Viktor (Optics Express)
Highly directive antennas with the ability of shaping radiation patterns in desired directions are essential for efficient on-chip optical communication with reduced cross talk. In this paper, we design and optimize three distinct broadband traveling-wave tantalum pentoxide antennas exhibiting highly directional characteristics. Our antennas contain a director and reflector deposited on a glass substrate, which are excited by a dipole emitter placed in the feed gap between the two elements. Full-wave simulations in conjunction with global optimization provide structures with an enhanced linear directivity as high as 119 radiating in the substrate. The high directivity is a result of the interplay between two dominant TE modes and the leaky modes present in the antenna director. Furthermore, these low-loss dielectric antennas exhibit a near-unity radiation efficiency at the operational wavelength of 780 nm and maintain a broad bandwidth. Our numerical results are in good agreement with experimental measurements from the optimized antennas fabricated using a two-step electron-beam lithography, revealing the highly directive nature of our structures. We envision that our antenna designs can be conveniently adapted to other dielectric materials and prove instrumental for inter-chip optical communications and other on-chip applications.
Keywords: tet_topic_opticalantenna

Procrastination in the Looking Glass of Self-Awareness: Can Gamified Self-Monitoring Reduce Academic Procrastination? - Klingsieck, Katrin B.; John, Thomas; Kundisch, Dennis (die hochschullehre)

Memes im Spanischunterricht - Ein populärkulturelles Phänomen aus dem Internet als Anlass für kommunikativ-ästhetisches Lernen - van der Valk, Stefanie (Hispanorama)

#Tuiteratura: Mit literarischen Kürzesttexten auf Twitter kreative Schreibanlässe schaffen - van der Valk, Stefanie (Der fremdsprachliche Unterricht Spanisch)

Die Bedeutung von Gläubigen für die Theologie

On polynomials with roots modulo almost all primes - Elsholtz, Ch.; Klahn, B.; Technau, Marc (Acta Arith.)

“Mama Always Had a Way of Explaining Things So I Could Understand”: A Dialogue Corpus for Learning to Construct Explanations - Wachsmuth, Henning; Alshomary, Milad (Proceedings of the 29th International Conference on Computational Linguistics)
As AI is more and more pervasive in everyday life, humans have an increasing demand to understand its behavior and decisions. Most research on explainable AI builds on the premise that there is one ideal explanation to be found. In fact, however, everyday explanations are co-constructed in a dialogue between the person explaining (the explainer) and the specific person being explained to (the explainee). In this paper, we introduce a first corpus of dialogical explanations to enable NLP research on how humans explain as well as on how AI can learn to imitate this process. The corpus consists of 65 transcribed English dialogues from the Wired video series 5 Levels, explaining 13 topics to five explainees of different proficiency. All 1550 dialogue turns have been manually labeled by five independent professionals for the topic discussed as well as for the dialogue act and the explanation move performed. We analyze linguistic patterns of explainers and explainees, and we explore differences across proficiency levels. BERT-based baseline results indicate that sequence information helps predicting topics, acts, and moves effectively.

Back to the Roots: Predicting the Source Domain of Metaphors using Contrastive Learning - Sengupta, Meghdut; Alshomary, Milad; Wachsmuth, Henning (Proceedings of the 2022 Workshop on Figurative Language Processing)

Verstand van zaken. Heterolinguïsme in de Nederlandstalige literatuur - Vandenbussche, Saskia (Vooys. Tijdschrift voor letteren)
Keywords: Heterolingualism; Literary Multilingualism; Dutch Literature

Zeitschriftenschau Der fremdsprachliche Unterricht Spanisch 73/2021 und 74/2021 - Büter, Mara Samira (Zeitschrift für romanische Sprachen und ihre Didaktik)

General stabilizer approach for constructing highly entangled graph states - Raissi, Zahra; Burchardt, Adam; Barnes, Edwin (Physical Review A)

Enhancing attitudes and self-efficacy toward inclusive teaching in physical education pre-service teachers: Results of a quasi-experimental study in physical education teacher education - Grimminger-Seidensticker, Elke; Seyda, Miriam (Frontiers in Education)

Wirksamkeit von SoTL im Rahmen hochschuldidaktischer Weiterbildung auf die Weiterentwicklung der (Lehr-)Kompetenz. Das Vertiefungsmodul im Paderborner Zertifikatsprogramm - Vöing, Nerea (Hochschullehre erforschen Innovative Impulse für das Scholarship of Teaching and Learning)

High-order embedding formalism, Noether's theorem on time scales and Eringen's nonlocal elastica - Hariz Belgacem, Khaled

Die Vergegenwärtigung höfischer Lustbarkeiten: André Félibiens 'Divertissements de Versailles' (1674/1676) - Steigerwald, Jörn (Im-Materiell. Kulturerbe-Studien für Eva-Maria Seng zum 60. Geburtstag)

Problematisches Sehen illusionärer Schönheit: die Armida-Episode in Torquato Tassos 'Gerusalemme liberata' - Steigerwald, Jörn (La Forme idéale à la Renaissance / Forma ideale durante il Rinascimento)

Die Geburt der italienischen Liebestragödie. Scipione Maffeis 'Merope'. - Steigerwald, Jörn (ZwischenSpielZeit. Das Theater der Frühaufklärung (1680-1730))

Der Zorn des ehrlichen Mannes. Die Neudeutung von Molières 'Misanthrope' in der 'Deutschen Schaubühne - Steigerwald, Jörn (Theater-Transfers. Akkulturationen des europäischen Dramas in Gottscheds 'Deutscher Schaubühne')

Transformationen des Heroismus in der Tragödie der Frühaufklärung. Geschlechterpoetik in Luise Gottscheds ‚Panthea‘. - Süwolto, Leonie (ZwischenSpielZeit. Das Theater der Frühaufklärung (1680-1740))

Elegische Liebestragödie. Johann Elias Schlegels "Die Trojanerinnen" (1737/47) - Puscher, Sahra (ZwischenSpielZeit. Das Theater der Frühaufklärung (1680-1730))

International Computer and Information Literacy Study 2018 (ICILS 2018) (Version 1) - Eickelmann, Birgit; Drossel, Kerstin; Labusch, Amelie

International Computer and Information Literacy Study 2018 (ICILS 2018) (Version 1) [Datensatz] - Eickelmann, Birgit; Drossel, Kerstin; Labusch, Amelie

On the (Limited) Generalization of MasterFace Attacks and Its Relation to the Capacity of Face Representations - Terhörst, Philipp; Bierbaum, Florian; Huber, Marco; Damer, Naser; Kirchbuchner, Florian; Raja, Kiran; Kuijper, Arjan (International IEEE Joint Conference on Biometrics, IJCB 2022, Abu Dhabi, United Arab Emirates, October 10-13, 2022)

On Evaluating Pixel-Level Face Image Quality Assessment - Huber, Marco; Terhörst, Philipp; Kirchbuchner, Florian; Damer, Naser; Kuijper, Arjan (2022 30th European Signal Processing Conference (EUSIPCO))

Jupyter Notebooks for Teaching, Learning, and Doing Data Science - Fleischer, Franz Yannik; Hüsing, Sven; Biehler, Rolf; Podworny, Susanne; Schulte, Carsten (Bridging the Gap: Empowering and Educating Today’s Learners in Statistics. Proceedings of the Eleventh International Conference on Teaching Statistics)
We report on our work with students in our data science courses, focusing on the analysis of students’ results. This study represents an in-depth analysis of students’ creation and documentation of machine learning models. The students were supported by educationally designed Jupyter Notebooks, which are used as worked examples. Using the worked example, students document their results in a so-called computational essay. We examine which aspects of creating computational essays are difficult for students to find out how worked examples should be designed to support students without being too prescriptive. We analyze the computational essays produced by students and draw consequences for redesigning our worked example.

Teaching and Learning Data-Driven Machine Learning with Educationally Designed Jupyter Notebooks - Fleischer, Franz Yannik; Biehler, Rolf; Schulte, Carsten (Statistics Education Research Journal)
This study examines modelling with machine learning. In the context of a yearlong data science course, the study explores how upper secondary students apply machine learning with Jupyter Notebooks and document the modelling process as a computational essay incorporating the different steps of the CRISP-DM cycle. The students’ work is based on a teaching module about decision trees in machine learning and a worked example of such a modelling process. The study outlines the students’ performance in carrying out the machine learning technically and reasoning about bias in the data, different data preparation steps, the application context, and the resulting decision model. Furthermore, the context of the study and the theoretical backgrounds are presented.
Keywords: Education; Statistics and Probability

Einleitung - Priesching, Nicole; Pahlke, Georg (Lorenz Jaeger als Seelsorger)

Lorenz Jaeger als Seelsorger

Einleitung - Priesching, Nicole; Kasprowski, Christian (Lorenz Jaeger als Kirchenpolitiker)

Einleitung - Priesching, Nicole; Pahlke, Georg (Lorenz Jaeger als Seelsorger)

„Ich klage an!“ Pfarrer Heinrich Ostermann am 19. Dezember 1945 an Erzbischof Lorenz Jaeger - Priesching, Nicole (Lorenz Jaeger als Seelsorger)

Theorie-Praxis-Relationierung im Praxissemester: Die Perspektive der Mentor*innen. - Caruso, Carina; Neuweg, Georg Hans; Wagner, Michael; Harteis, Christian (Zeitschrift für Erziehungswissenschaft)
In der Mehrheit der deutschen Bundesländer ist ein Langzeitpraktikum (Praxissemester) Bestandteil der Lehramtsstudiengänge. Es zielt insbesondere darauf, Theorie und Praxis miteinander in Beziehung zu setzen. Trotz der gewichtigen Rolle, die den Mentor*innen dabei zugeschrieben wird, ist deren Perspektive noch wenig untersucht. Die empirisch auffindbaren Unterschiede in der Betreuung Studierender könnten u. a. auf unterschiedliche Vorstellungen von der Beziehung zwischen Theorie und Praxis seitens der Mentor*innen zurückzuführen sein. Diese Vorstellungen interessieren in der im Folgenden dargestellten explorativen Interviewstudie, deren Daten einer strukturierenden Inhaltsanalyse unterzogen wurden. Nachstehenden Forschungsfragen wird nachgegangen: 1) Sind die Mentor*innen auf die Aufgabe der Verknüpfung von Theorie und Praxis vorbereitet? 2) Werden in den Erzählungen der Mentor*innen zu gelingenden und misslingenden Betreuungserfahrungen Theorie-Praxis-Relationierungsfiguren sichtbar, wenn ja, welche und zeigen sich Bemühungen der Verknüpfung von Theorie und Praxis? 3) Werden in den Erzählungen der Mentor*innen zur eigenen Lerngeschichte Theorie-Praxis-Relationierungsfiguren sichtbar, wenn ja, welche und welche relative Rolle spielt das Ausbildungswissen aus Sicht der Mentor*innen für die Entwicklung ihres Könnens? 4) Welches Wissensverständnis der Mentor*innen zeigt sich in den Transkripten und welche Relevanz wird Wissen im Vergleich zu Erfahrung, Reflexion von Erfahrung und Persönlichkeit zugeschrieben? Es zeigt sich, dass die Mentor*innen das Theorie-Praxis-Verhältnis in den Gesprächen selten thematisieren, die Begriffe „Wissen“ und „Können“ synonym verwenden und der Erfahrung für die Entwicklung von Können eine höhere Relevanz beimessen als dem didaktischen und pädagogischen Ausbildungswissen.
Keywords: Lehrer*innenbildung; Mentoring; Praxissemester; Professionalisierung; Theorie-Praxis-Relationierung / Teacher training; Mentoring; Internship; Professionalization; Theory-practice-relation

Die Theologie und ihre Akteure" & "Praktizierte Glaubensreflexion als Erkenntnisort der Theologie - Grössl, Johannes (Die Bedeutung von Gläubigen für die Theologie)

Gottes Immanenz denken – auch im personalen Theismus? - Grössl, Johannes (Mit dem Herzen denken. Konturen einer leidenschaftlichen Theologie der Welt [FS Roman Siebenrock])

Erkenntnis durch Offenbarung als Gefahr für menschliche Autonomie? - Grössl, Johannes (Problemfall Offenbarung. Grund – Konzepte – Erkennbarkeit)

Extra narrationem nulla salus. Perspektiven eines narrativitätstheoretischen Ansatzes für die christliche Soteriologie - Grössl, Johannes; Kronau, Johannes (Münchner Zeitschrift für Katholische Theologie)

Beethoven in the House: Digital Studies of Domestic Music Arrangements - Page, Kevin R.; Kepper, Johannes; Siegert, Christine; Hankinson, Andrew; Lewis, David (Music Encoding Conference Proceedings 2021)
Performance of music in the home was the means by which most works were received before the advent of audio recordings and broadcasts, yet the notation sources that form our primary record of this culture have not been the subject of comprehensive or methodical study. Choices made by arrangers adapting music for domestic consumption – of instrumentation, abbreviation, or simplification – reflect the musical life of the 19th century, and can inform our understanding alongside contemporary accounts such as newspapers, adverts, and diaries. This position paper gives the background, motivation, and proposed approach of research currently being undertaken within the Beethoven in the House project. This will include a study of Steiner editions of Beethoven’s 7th and 8th Symphonies and Wellingtons Sieg, making a detailed comparison between arrangements, systematically identifying a core common to multiple versions, and asking if this reflects the stated values of the publisher. A second survey will look for patterns across a larger sample of lesser-known and poorly catalogued scores, collating emergent indicators of arrangers’ motivations within a narrative of the domestic market – the music industry of its day. Both studies will innovate digital methods which characterise arrangements as music encodings, including ‘sparse’ approaches to notation and annotation.
Keywords: BitH; mec-proceedings; mec-proceedings-2021

Encoding Genetic Processes II - Cox, Susanne; Kepper, Johannes (Music Encoding Conference Proceedings 2021)

A model for annotating musical versions and arrangements across multiple documents and media - Lewis, David; Shibata, Elisabete; Saccomano, Mark; Rosendahl, Lisa; Kepper, Johannes; Hankinson, Andrew; Siegert, Christine; Page, Kevin (9th International Conference on Digital Libraries for Musicology)
Keywords: BitH

Educational Management on regional levels. Implications for vocational education - Daniel-Söltenfuß, Desiree; Hagemeier, Daniel; Ludolph, Fabian

Die Konstruktion von Geschäftsmodellen für nachhaltiges Wirtschaften: (k)eine exklusive Aufgabe des Managements?! - Schlömer, Tobias; Kiepe, Karina; Thrun, Tim (Intrapreneurship)

Geschäftsmodelle als Lerngegenstände der betrieblichen Berufsausbildung - Kiepe, Karina (Ausbilder Handbuch)

Javier Marías: Berta Isla - Schmitz, Sabine (Wegmarken der spanischen Literatur des 21. Jahrhunderts)

Die Glaskunst in der Belgien-Leselounge der Universitätbibliothek Paderborn - Schmitz, Sabine; Peters, Wilhelm; Peters, Dorothea (Paderborner Universitätsreden)

‚Schreibsensibel‘ Geschichte unterrichten: Fachspezifische Textkompetenz als Gegenstand und Medium des historischen Lernens - Hartung, Olaf; Memminger, Josef (Schreiben fachübergreifend fördern. Grundlagen und Praxisanregungen für Schule, Unterricht und Lehrerinnen- und Lehrerbildung)

Editorial: Anschaulichkeit – Wissen. Macht. Alternativen. - Eckel, Julia; Linseisen, Elisa (Rabbit Eye – Zeitschrift für Filmforschung)
Keywords: Anschaulichkeit; Anschauung; Film; Epistemologie audiovisueller Medien; Erklärbarkeit; Anschauen; Sichtbarkeit; Unsichtbarkeit

Rabbit Eye: Anschaulichkeit (Rabbit Eye - Zeitschrift für Filmforschung)

Nano-FTIR and chemical force analysis of electrografted aryldiazonium salts on ODT-microcontact printed Au-surfaces - Su, Jiangling; González Orive, Alejandro; Grundmeier, Guido (Applied Surface Science)
Keywords: Surfaces; Coatings and Films; Condensed Matter Physics; Surfaces and Interfaces; General Physics and Astronomy; General Chemistry

Oxidation stability of chromium aluminum oxynitride hard coatings - Bobzin, K.; Kalscheuer, C.; Grundmeier, Guido; de los Arcos, T.; Kollmann, S.; Carlet, M. (Surface and Coatings Technology)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Surfaces and Interfaces; Condensed Matter Physics; General Chemistry

Thin Organic‐Inorganic Anti‐Fouling Hybrid‐Films for Microreactor Components - Neßlinger, Vanessa; Welzel, Stefan; Rieker, Florian; Meinderink, Dennis; Nieken, Ulrich; Grundmeier, Guido (Macromolecular Reaction Engineering)
Keywords: Polymers and Plastics; General Chemical Engineering; General Chemistry

Calibration of 3D scan trajectories for an industrial computed tomography setup with 6-DOF object manipulator system using a single sphere - Butzhammer, Lorenz; Müller, Andreas Michael; Hausotte, Tino (Measurement Science and Technology)
In industrial x-ray computed tomography (CT), the application of more complex scan paths in comparison to the typical circular trajectory (${360}^{°}$ rotation of the measurement object) can extend the potential of CT. One way to enable such 3D scan trajectories is to use a 6-degrees-of-freedom (DOF) object manipulator system. In our case, a hexapod is mounted on top of the rotary table of a commercial CT scanner. This allows for adaptive tilting of the measurement object during the scan. For high accuracy, the geometry calibration of such setups is typically done using the x-ray projections of a calibrated multi-sphere object. Contrary to this, here, we demonstrate a procedure that is based on only a single sphere and can therefore experimentally be implemented with low effort. Using the intrinsic geometry parameters of the CT device as prior information, the hexapod coordinate system with respect to the CT machine coordinate system is determined by means of a one-step optimization approach. The resulting parameters are used to calculate projection matrices that enable the volume reconstruction for 3D scan trajectories. The method is validated using simulated x-ray images and experimental investigations including dimensional measurements. For the used setup, geometric measurement results for 3D scan trajectories that are calibrated with the presented method show in sum increased errors compared to the circular scans. A limited pose accuracy of the manipulator system is discussed as a potential cause. The results nevertheless indicate that the presented method is generally feasible for dimensional CT measurements provided that the pose accuracy is sufficient. The calibration procedure can therefore be a low-cost and easier to implement alternative compared to trajectory calibration methods based on multi-sphere objects, but with a tendency towards lower measurement accuracy. The methodology can in principle be transferred to different setups with 6-DOF manipulator systems, e.g. C-arm CT devices with a robot arm.
Keywords: Applied Mathematics; Instrumentation; Engineering (miscellaneous)

Remote epitaxy of In(x)Ga(1-x)As(001) on graphene covered GaAs(001) substrates - Henksmeier, Tobias; Schulz, Johann Friedemann; Kluth, Elias; Feneberg, Martin; Goldhahn, Rüdiger; Sanchez, Ana M.; Voigt, Markus; Grundmeier, Guido; Reuter, Dirk (Journal of Crystal Growth)

Bridging HPC Communities through the Julia Programming Language - Churavy, Valentin; Godoy, William F; Bauer, Carsten; Ranocha, Hendrik; Schlottke-Lakemper, Michael; Räss, Ludovic; Blaschke, Johannes; Giordano, Mosè; Schnetter, Erik; Omlin, Samuel; Vetter, Jeffrey S; Edelman, Alan
The Julia programming language has evolved into a modern alternative to fill existing gaps in scientific computing and data science applications. Julia leverages a unified and coordinated single-language and ecosystem paradigm and has a proven track record of achieving high performance without sacrificing user productivity. These aspects make Julia a viable alternative to high-performance computing's (HPC's) existing and increasingly costly many-body workflow composition strategy in which traditional HPC languages (e.g., Fortran, C, C++) are used for simulations, and higher-level languages (e.g., Python, R, MATLAB) are used for data analysis and interactive computing. Julia's rapid growth in language capabilities, package ecosystem, and community make it a promising universal language for HPC. This paper presents the views of a multidisciplinary group of researchers from academia, government, and industry that advocate for an HPC software development paradigm that emphasizes developer productivity, workflow portability, and low barriers for entry. We believe that the Julia programming language, its ecosystem, and its community provide modern and powerful capabilities that enable this group's objectives. Crucially, we believe that Julia can provide a feasible and less costly approach to programming scientific applications and workflows that target HPC facilities. In this work, we examine the current practice and role of Julia as a common, end-to-end programming model to address major challenges in scientific reproducibility, data-driven AI/machine learning, co-design and workflows, scalability and performance portability in heterogeneous computing, network communication, data management, and community education. As a result, the diversification of current investments to fulfill the needs of the upcoming decade is crucial as more supercomputing centers prepare for the exascale era.

Accessibility properties of abnormal geodesics in optimal control illustrated by two case studies - Bonnard, Bernard; Rouot, Jérémy; Wembe Moafo, Boris Edgar (Mathematical Control and Related Fields)
Keywords: Applied Mathematics; Control and Optimization; General Medicine

Abnormal geodesics in 2D-Zermelo navigation problems in the case of revolution and the fan shape of the small time balls - Bonnard, B.; Cots, O.; Gergaud, J.; Wembe Moafo, Boris Edgar (Systems & Control Letters)
Keywords: Electrical and Electronic Engineering; Mechanical Engineering; General Computer Science; Control and Systems Engineering

Frontal theta power increases during table tennis play – indications for neurophysiological demands during open-skill sports? - Büchel, Daniel; Visser, Anton; Lehmann, Tim; Baumeister, Jochen

Surface Instability Modulates Cortical Information Processing In Multi-Joint Compound Movements - Lehmann, Tim; Visser, Anton; Havers, Tim; Büchel, Daniel; Baumeister, Jochen

Engaging with self-tracking applications: how do users respond to their performance data? - Constantiou, Ioanna; Mukkamala, Alivelu; Sjöklint, Mimmi; Trier, Matthias (European Journal of Information Systems)
Keywords: Library and Information Sciences; Information Systems

Model droplet formation in extensional filament stretching within a Filament Extension Atomizer - Neukötter, Moritz; Jesinghausen, Steffen; Schmid, Hans-Joachim (Rheologica Acta)
Abstract Further innovation in the field of selective laser sintering (SLS) is strongly connected to the availability of new materials since the market is dominated by polyamide 12 (>90%). The aim of this publication is to develop a descriptive model for the droplet formation process in a Filament Extension Atomizer to predict the applicability to exploit further polymers for the SLS process. The feasibility was tested, investigated and characterized using a “Dripping out of a nozzle” setup for uniaxial extension. The droplet formation process was then observed via high-speed camera imaging and classified for certain parameters. The experiments were carried out using semi-diluted polyethylene oxide (600–4000 kg/mol), glycerol and water solutions as model fluids. Driven by the Plateau-Rayleigh instability, different types of spherical droplets were observed and various droplet formation mechanisms demonstrated and analyzed. Based on the experimental results, a predictive model is derived to describe various essential parameters.
Keywords: Rheology; SLS; Lasersintering; exensional rheology

Language in the Age of Mechanical Reproduction - Thomas, Sven (Technology and Language)

Experimental Investigation of the Pressure Dependence of Iso-Octane Combustion - Shaqiri, S.; Kaczmarek, D.; vom Lehn, F.; Beeckmann, J.; Pitsch, H.; Kasper, Tina (Frontiers in Energy Research)
Iso-octane is frequently used as a surrogate fuel or as a component in primary reference fuel blends when low-temperature combustion strategies in engines are investigated. To develop control strategies for these engines, the reaction kinetics of iso-octane must be known starting from the low temperatures and intermediate pressures before ignition to the high temperatures and pressures of combustion. This work adds new experimental data sets to the validation data for reaction mechanism development by investigating the oxidation of iso-octane in stoichiometric mixtures in a flow reactor at pressures of p = 1, 10, and 20 bar and 473K ≤ T ≤ 973 K. The experimental data are compared to simulations with recent reaction mechanisms [Atef et al., Combustion and Flame 178, (2017), Bagheri et al., Combustion and Flame 212, (2020), Cai et al., Proceedings of the Combustion Institute 37, (2018), Fang et al., Combustion and Flame 214, (2020)]. The comparison between experimental and simulated mole fractions as function of temperature show reasonable agreement for all investigated pressures. In particular, the experimentally observed onset of low-temperature reactivity above a certain pressure, the shift of the negative temperature coefficient (NTC) regime with increasing pressure to higher temperatures, and the acceleration of the high-temperature chemistry are captured well in the simulations. Deviations between experimental and simulated results are discussed in detail for the reactivity of iso-octane and some key intermediates such as 2,2,4,4-tetramethyl-tetrahydrofuran, iso-butene and acetone at low temperatures.
Keywords: Economics and Econometrics; Energy Engineering and Power Technology; Fuel Technology; Renewable Energy; Sustainability and the Environment

Nitrous acid in high-pressure oxidation of CH4 doped with nitric oxide: Challenges in the isomer-selective detection and quantification of an elusive intermediate - Hoener, Martin; Kasper, Tina (Combustion and Flame)
Keywords: General Physics and Astronomy; Energy Engineering and Power Technology; Fuel Technology; General Chemical Engineering; General Chemistry

Experimental and kinetic modeling study of the positive ions in premixed ethylene flames over a range of equivalence ratios - Knyazkov, Denis A.; Cherepanov, Andrey V.; Kiselev, Vitaly G.; Gerasimov, Ilya E.; Kasper, Tina; Shmakov, Andrey G. (Proceedings of the Combustion Institute)
Keywords: Physical and Theoretical Chemistry; Mechanical Engineering; General Chemical Engineering

Directional dependence of the mechanical properties of structural adhesive joints with curing-induced pre-deformations - Beule, Felix; Teutenberg, Dominik; Meschut, Gerson (Proceedings of the Institution of Mechanical Engineers, Part D: Journal of Automobile Engineering)
Owing to the implementation of multi-material construction methods in modern lightweight construction and the associated use of adhesive bonding technology, thermally induced relative displacements of the joining partners occur during the curing process. The resulting extremely complex thermo-chemo-mechanical stresses can influence the properties of the adhesive layers and reduce the load-bearing capacity. In this study, experiments are conducted to examine the influence of process-related thermal relative displacements on the mechanical properties of adhesives. The results show an anisotropy of the mechanical properties of the pre-deformed adhesive layers, depending on the magnitude and direction of the relative displacement.
Keywords: Mechanical Engineering; Aerospace Engineering

Activation effect of ozone and DME on the partial oxidation of natural gas surrogates and validation of pressure-dependent ozone decomposition - Kaczmarek, D.; Bierkandt, T.; Rudolph, C.; Grimm, S.; Shaqiri, S.; Höner, M.; Gaiser, N.; Atakan, B.; Köhler, M.; Hemberger, P.; Kasper, Tina (Applications in Energy and Combustion Science)
Keywords: Fuel Technology; Energy (miscellaneous); Chemical Engineering (miscellaneous)

Kinetic investigation of the ozone-assisted partial oxidation of fuel-rich natural gas mixtures at elevated pressure - Kaczmarek, Dennis; Rudolph, Charlotte; Atakan, Burak; Kasper, Tina (Proceedings of the Combustion Institute)
Keywords: Physical and Theoretical Chemistry; Mechanical Engineering; General Chemical Engineering

A combustion chemistry study of tetramethylethylene in a laminar premixed low-pressure hydrogen flame - Bierkandt, Thomas; Hemberger, Patrick; Oßwald, Patrick; Gaiser, Nina; Hoener, Martin; Krüger, Dominik; Kasper, Tina; Köhler, Markus (Proceedings of the Combustion Institute)
Keywords: Physical and Theoretical Chemistry; Mechanical Engineering; General Chemical Engineering

Functionality Study of an Optical Measurement Concept for Local Force Signal Determination in High Strain Rate Tensile Tests - Böhnke, Max; Unruh, Eduard; Sell, Stanislaw; Bobbert, Mathias; Hein, David; Meschut, Gerson (Key Engineering Materials)
Many mechanical material properties show a dependence on the strain rate, e.g. yield stress or elongation at fracture. The quantitative description of the material behavior under dynamic loading is of major importance for the evaluation of crash safety. This is carried out using numerical methods and requires characteristic values for the materials used. For the standardized determination of dynamic characteristic values in sheet metal materials, tensile tests performed according to the guideline from [1]. A particular challenge in dynamic tensile tests is the force measurement during the test. For this purpose, strain gauges are attached on each specimen, wired to the measuring equipment and calibrated. This is a common way to determine a force signal that is as low in vibration and as free of bending moments as possible. The preparation effort for the used strain gauges are enormous. For these reasons, an optical method to determine the force by strain measurement using DIC is presented. The experiments are carried out on a high speed tensile testing system. In combioantion with a 3D DIC high speed system for optical strain measurement. The elastic deformation of the specimen in the dynamometric section is measured using strain gauges and the optical method. The measured signals are then compared to validate the presented method. The investigations are conducted using the dual phase steel material HCT590X and the aluminum material EN AW-6014 T4. Strain rates of up to 240 s-1 are investigated.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Development of a Modified Punch Test for Investigating the Failure Behavior in Sheet Metal Materials - Böhnke, Max; Bielak, Christian Roman; Bobbert, Mathias; Meschut, Gerson (The Minerals, Metals & Materials Series)

Experimental and numerical investigation of the influence of multiaxial loading conditions on the failure behavior of clinched joints - Böhnke, Max; Bielak, Christian Roman; Bobbert, Mathias; Meschut, Gerson (Proceedings of the Institution of Mechanical Engineers, Part L: Journal of Materials: Design and Applications)

A Comprehensive Study on Face Recognition Biases Beyond Demographics - Terhörst, Philipp; Kolf, Jan Niklas; Huber, Marco; Kirchbuchner, Florian; Damer, Naser; Moreno, Aythami Morales; Fierrez, Julian; Kuijper, Arjan (IEEE Transactions on Technology and Society)

Verification of Sitter Identity Across Historical Portrait Paintings by Confidence-aware Face Recognition - Huber, Marco; Terhörst, Philipp; Luu, Anh Thi; Kirchbuchner, Florian; Damer, Naser (26th International Conference on Pattern Recognition, ICPR 2022, Montreal, QC, Canada, August 21-25, 2022)

An Attack on Facial Soft-Biometric Privacy Enhancement - Roig, Dailé Osorio; Rathgeb, Christian; Drozdowski, Pawel; Terhörst, Philipp; Struc, Vitomir; Busch, Christoph (IEEE Trans. Biom. Behav. Identity Sci.)

Development of operational and demand-oriented firefighting equipment - Hanses, Hendrik; Horwath, Ilona (Materials Today: Proceedings)
Keywords: General Medicine

Does private firms’ disclosure affect public peers’ information environment? - Beyer, Bianca; Flagmeier, Vanessa; Kosi, Urska

Testing, modelling, and parameter identification for adhesively bonded joints under the influence of temperature - Schmelzle, Lars; Striewe, Marius; Mergheim, Julia; Meschut, Gerson; Possart, Gunnar; Teutenberg, Dominik; Hein, David; Steinmann, Paul (Journal of Adhesion Science and Technology)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Surfaces and Interfaces; Mechanics of Materials; General Chemistry

Robotergestütztes manuelles mechanisches Fügen – RoboterFügen - Neumann, Stefan; Meschut, Gerson; Schmatz, Frederik; Flügge, Wilko

Von der Präsenz-Blockveranstaltung zum Blended Learning-Konzept - Graefe, Grit; Temmen, Katrin (Hochschullehre erforschen)

Applying XAI to an AI-based system for candidate management to mitigate bias and discrimination in hiring - Hofeditz, Lennart; Clausen, Sünje; Rieß, Alexander; Mirbabaie, Milad; Stieglitz, Stefan (Electronic Markets (ELMA))
Abstract Assuming that potential biases of Artificial Intelligence (AI)-based systems can be identified and controlled for (e.g., by providing high quality training data), employing such systems to augment human resource (HR)-decision makers in candidate selection provides an opportunity to make selection processes more objective. However, as the final hiring decision is likely to remain with humans, prevalent human biases could still cause discrimination. This work investigates the impact of an AI-based system’s candidate recommendations on humans’ hiring decisions and how this relation could be moderated by an Explainable AI (XAI) approach. We used a self-developed platform and conducted an online experiment with 194 participants. Our quantitative and qualitative findings suggest that the recommendations of an AI-based system can reduce discrimination against older and female candidates but appear to cause fewer selections of foreign-race candidates. Contrary to our expectations, the same XAI approach moderated these effects differently depending on the context.
Keywords: Management of Technology and Innovation; Marketing; Computer Science Applications; Economics and Econometrics; Business and International Management

The Investigator’s Dilemma - A Review of Social Media Analytics Research Ethics in Information Systems - Marx, Julian; Mirbabaie, Milad (Australasian Journal of Information Systems)
Social media have become not only integral parts of our private and professional lives, but also an indispensable source of data for empirical research across a variety of academic disciplines. Applying a Social Media Analytics (SMA) methodology, however, imposes heavy ethical challenges on researchers. Scholars in the Information Systems (IS) discipline must deal with a patchwork of ethical frameworks, regulations, and (missing) institutional support. To initiate a debate on how to develop a common understanding of SMA research ethics, this paper compiles a scoping review of extant literature and suggests a research agenda for IS scholarship on this matter. The review yields a total of eight fundamental principles of ethical SMA research, which provide a starting point to guiding individual researchers towards more ethical conduct. At the same time, this work unearths a multitude of intricate dilemmas that are currently unresolved. The findings of this review will encourage IS scholarship to find its own voice in the debate about social media research ethics.
Keywords: Information Systems and Management; Human-Computer Interaction; Business; Management and Accounting (miscellaneous); Information Systems

How crises are different - Design principles for conversational agents to support Emergency Management Agencies - Stieglitz, Stefan; Hofeditz, Lennart; Brünker, Felix; Ehnis, Christian; Mirbabaie, Milad; Ross, Björn (International Journal of Information Management)
Keywords: Library and Information Sciences; Computer Networks and Communications; Information Systems

Ethics and AI in Information Systems Research - Mirbabaie, Milad; Brendel, Alfred B.; Hofeditz, Lennart (Communications of the Association for Information Systems)
Keywords: Information Systems

Catchword: Digital Detox - Mirbabaie, Milad; Stieglitz, Stefan; Marx, Julian (Business & Information Systems Engineering)
Keywords: Information Systems

Review of Design-Oriented Green Information Systems Research - Brendel, Alfred Benedikt; Chasin, Friedrich; Mirbabaie, Milad; Riehle, Dennis M.; Harnischmacher, Christine (Sustainability)
Green IS (GIS) research addresses environmental challenges brought on by climate change and the need to preserve the natural environment. Within this scope, design-oriented research, most notably within the Design Science Research (DSR) community, aims to provide solutions to these environmental challenges in the form of novel artifacts. The resulting IS solutions are valuable instruments for reducing emissions, increasing energy efficiency, and mitigating waste. Over the past 14 years, the IS research community was called upon multiple times to focus on designing solutions suitable for facilitating sustainability. However, it is unclear how these calls for action resonated within the design-oriented research community. Against this background, we analyzed the landscape of design-oriented GIS research by looking at 60 different GIS studies that have designed and evaluated an artifact. By analyzing these publications, we were able to make six observations. Based on these observations, we discuss how design-oriented GIS research can evolve to live up to the expectations of creating an immediate positive environmental impact.
Keywords: Management; Monitoring; Policy and Law; Renewable Energy; Sustainability and the Environment; Geography; Planning and Development

Click me…! The influence of clickbait on user engagement in social media and the role of digital nudging - Jung, Anna-Katharina; Stieglitz, Stefan; Kissmer, Tobias; Mirbabaie, Milad; Kroll, Tobias (PLOS ONE)
Clickbait to make people click on a linked article is commonly used on social media. We analyze the impact of clickbait on user interaction on Facebook in the form of liking, sharing and commenting. For this, we use a data set of more than 4,400 Facebook posts from 10 different news sources to analyze how clickbait in post headlines and in post text influences user engagement. The results of our study revealed that certain features (e.g., unusual punctuation and common clickbait phrases) increase user interaction, whereas others decrease engagement with Facebook posts. We further use our results to discuss the potential role of digital nudging in the context of clickbait. Our results contribute to understanding and making use of the effect of different framings in social media.
Keywords: Multidisciplinary

Rumor Correction in Social Media Crisis Communication: A Case of Connective Sense-Breaking - Mirbabaie, Milad; Marx, Julian; Reimann, Annette (AIS Transactions on Human-Computer Interaction)
Keywords: General Medicine

How News Websites Refer to Twitter: A Content Analysis of Twitter Sources in Journalism - Kapidzic, Sanja; Neuberger, Christoph; Frey, Felix; Stieglitz, Stefan; Mirbabaie, Milad (Journalism Studies)
Keywords: Communication

Trust Me, I’m an Influencer! - A Comparison of Perceived Trust in Human and Virtual Influencers - Hofeditz, Lennart; Nissen, Anika; Schütte, Reinhard; Mirbabaie, Milad (30th European Conference on Information Systems - New Horizons in Digitally United Societies, ECIS 2022, Timisoara, Romania, June 18-24, 2022)

A Design Science Artefact for Cyber Threat Detection and Actor Specific Communication - Eyilmez, Kaan; Basyurt, Ali Sercan; Stieglitz, Stefan; Fuchss, Christoph; Kaufhold, Marc-André; Reuter, Christian; Mirbabaie, Milad (Australasian Conference on Information Systems (ACIS))
Keywords: Student; Security; Projekt-CYWARN

Automating Crisis Communication in Public Institutions–Towards Ethical Conversational Agents That Support Trust Management - Hofeditz, Lennart; Mirbabaie, Milad; Erle, Lukas; Knoßalla, Eileen; Timm, Lara (Proceedings of the 17th International Conference on Wirtschaftsinformatik)

Credibility of Cyber Threat Communication on Twitter–Expert Evaluation of Indicators for Automated Credibility Assessment - Basyurt, Ali Sercan; Fromm, Jennifer; Stieglitz, Stefan; Mirbabaie, Milad (Proceedings of the 17th International Conference on Wirtschaftsinformatik)

From Dark Patterns to Digital Sludging–Mapping the Ethical Debate on Controversial Persuasive System Design - Clausen, Sünje; Marx, Julian; Mirbabaie, Milad; Stieglitz, Stefan (Proceedings of the 43rd International Conference on Information Systems (ICIS))

Knowledge Work ‘Unplugged’-Digital Detox Effects on ICT Demands, Job Performance and Satisfaction - Mirbabaie, Milad; Braun, Lea-Marie; Marx, Julian (Proceedings of the 17th International Conference on Wirtschaftsinformatik)